The NuRD complex component p66 suppresses photoreceptor neuron regeneration in planarians. Issue 3 (18th August 2016) - Vásquez‐Doorman, Constanza; Petersen, Christian P.
Abstract: Regeneration involves precise control of cell fate to produce an appropriate complement of tissues formed within a blastema. Several chromatin‐modifying complexes have been identified as required for regeneration in planarians, but it is unclear whether this class of molecules uniformly promotes the production of differentiated cells. We identify a function for p66, encoding a DNA‐binding protein component of the NuRD (nucleosome remodeling and deacetylase) complex, as well as the chromodomain helicase chd4, in suppressing production of photoreceptor neurons (PRNs) in planarians. This suppressive effect appeared restricted to PRNs because p66 inhibition did not influence numbers of eye pigment cup cells (PCCs) and decreased numbers of brain neurons and epidermal progenitors. PRNs from p66(RNAi) animals differentiated with some abnormalities but nonetheless produced arrestin+ projections to the brain. p66 inhibition produced excess ovo+otxA + PRN progenitors without affecting numbers of ovo+otxA − PCC progenitors, and ovo and otxA were each required for the p66(RNAi) excess PRN phenotype. Together these results suggest that p66 acts through the NuRD complex to suppress PRN production by limiting expression of lineage‐specific transcription factors.